Fast Facts: Molecular Profiling in Solid Tumors - Parneet, Cheema; Elena, Garralda; Brandon S., Sheffield; Pasquale, Pisapia (S. Karger, 2023)
Identifying tumor-specific molecular aberrations via molecular profiling is vital for the use of targeted therapies. Understanding a patient's unique tumor genetics provides predictive and prognostic information that enables a personalized care plan to be put in place, improving outcomes and minimizing ineffective treatments.'Fast Facts: Molecular Profiling in Solid Tumors'provides a firm knowledge foundation of somatic molecular profiling methodologies, key information to help with the use of molecular profiling in daily practice and advice on communicating with patients about molecular testing and results.